Impure public technologies and environmental policy - Dirk T. G. Rübbelke; Anil Markandya (Fondazione Eni Enrico Mattei (FEEM), 2008)
Analyses of public goods regularly address the case of pure public goods. However, a large number of (international) public goods exhibit characteristics of different degrees of publicness, i.e. they are impure public goods. In our analysis of transfers helping to overcome the inefficient provision of such goods, we therefore apply the Lancastrian characteristics approach. In contrast to the existing literature, we consider the case of a continuum of impure public goods. We employ the example of international conditional transfers targeting to overcome suboptimal low climate protection efforts by influencing the abatement technology choice of countries.
Keywords: H87; Q54; 330; Impure Public Goods; Lancastrian Characteristics Approach; Conditional Transfers; Ancillary Benefits of Climate Policy